A közbeszerzési szerződések módosítása - Tarkó, Izabel Ágnes (Debreceni Jogi Műhely, 2018)
In the recent study we examine the Public Procurement Law as a clear framework for possibilities to amend procurement contracts after completion of the tender procedure in Hungary. Under the amendments, further modification of procurement contracts is permitted if the modifications are non-substantial; or substantial, but in exceptional circumstances could apply regardless of whether the modifications are substantial or not. Substantial modifications are modifications that would have made a difference to bidding or participation or selection of tenderers, or where the economic balance – risks and their compensatory measures – are changed in the favour of the supplier, or including work not provided for by the initial contract, replacing the supplier. Substantial modifications are permitted only if the tender documentation has clearly provided for the possibility and if the conditions on which the modifications plus the extent and nature of possible modifications are acceptable, or if the modifications are made within a specific negotiating procedure, or if the supplier is replaced due to restructuring or transfer of enterprises by law. So far the contracting authorities are very limited in the scope of modifications. This meant the Act CXLIII of 2015 on Public Procurement provides quite strict conditions to bind economically more successful contracts. Additionally we examine the new EU Directive on public procurement and Case Pressetext (C-454/06) of the European Court provides the guidelines which even substantial modifications of contracts are permitted without carrying out a new tender procedure.